1971
DOI: 10.1111/j.1399-3054.1971.tb01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Occurrence of Indole‐3‐Acetic‐Acid in Buds of Pinus silvestris

Abstract: Studies with a fluorescence spectrophotometer and gas chromatography confirm earlier results that IAA occurs in buds and sprouting shoots of Scots pine. IAA could be found during the whole vegetation period but not during winter dormancy. The largest amount was obtained during shoot growth in spring and early summer. During the most intensive elongation phase, a gradient could be found in the concentration of auxin with the highest amount in the basal part and a decreasing concentration upwards in the shoot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Because most quantitative evidence in the past has been acquired from bioassays, reported amounts of endogenous IAA in various plant species, especially conifers, must be evaluated cautiously. The quantity of endogenous IAA found in spring extracts of Douglas fir is in the midrange of values stated in the literature for different species (1)(2)(3)6).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Because most quantitative evidence in the past has been acquired from bioassays, reported amounts of endogenous IAA in various plant species, especially conifers, must be evaluated cautiously. The quantity of endogenous IAA found in spring extracts of Douglas fir is in the midrange of values stated in the literature for different species (1)(2)(3)6).…”
Section: Discussionmentioning
confidence: 85%
“…In the last 10 years, GLC has been added for final separation and analysis of plant extracts because of its ability to fractionate volatilized components in a specific and reproducible fashion (1,3, 21,27). If several stationary phases of differing physical character are included, the data produced are even more reliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher level of auxin has been found in growing pine shoots (1) as compared to bean plants (9,22). Assay by a biotest indicated that growing aspen shoot tissue contained about 50 times the auxin content of growing pea shoots (5).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2b). The sequence in root length suggests that removal of buds at the same time removed a shoot-to-root signal, which had to be synthesized before root elongation could continue [1,5,20]. Conifer buds are high in auxin, which might be lowered by the debudding proces [1,6,27].…”
Section: Discussionmentioning
confidence: 99%